1997
DOI: 10.1046/j.1365-2036.1997.90262000.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: the dietary management of Crohn's disease

Abstract: Enteral feeding has been shown to be as effective as primary therapy for Crohn's disease, but it requires high patient motivation, may be unpalatable and is expensive. However, in adolescents with growth failure and when corticosteroid therapy is contra‐indicated or has failed, it may become the treatment of choice. Furthermore, dietary therapy allows circumvention of the adverse side‐effects of repeated courses of steroids.A number of different hypotheses have been proposed to explain the effect of enteral fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 98 publications
1
35
1
2
Order By: Relevance
“…34 Many individuals identified some foods as possibly disease activity and believed that their exclusion could lead to prolongation of disease remission. 35 Dietetic supervision during food testing is important to avoid the detrimental effects on nutrient and micronutrient intake. 35 In our study, less than half of patients reported having received dietetic counselling provide from their gastroenterologist or dietetician.…”
Section: Dietary Behavior (Table 5)mentioning
confidence: 99%
See 1 more Smart Citation
“…34 Many individuals identified some foods as possibly disease activity and believed that their exclusion could lead to prolongation of disease remission. 35 Dietetic supervision during food testing is important to avoid the detrimental effects on nutrient and micronutrient intake. 35 In our study, less than half of patients reported having received dietetic counselling provide from their gastroenterologist or dietetician.…”
Section: Dietary Behavior (Table 5)mentioning
confidence: 99%
“…35 Dietetic supervision during food testing is important to avoid the detrimental effects on nutrient and micronutrient intake. 35 In our study, less than half of patients reported having received dietetic counselling provide from their gastroenterologist or dietetician. The other sources included general practitioners, family, internet, friends and other IBD patients.…”
Section: Dietary Behavior (Table 5)mentioning
confidence: 99%
“…However, there aren't enough data to support the substitution of drug therapy by EN 50 . Beside other mechanisms, EN decreases CD activity by decreasing the synthesis of inflammatory mediators and by providing specific nutrients 16,32 .…”
Section: Enteral Nutrition (En)mentioning
confidence: 99%
“…Recently, excellent literature reviews 50,66,81 and meta-analyses 22,34 concerning primary NT of IBD have been published.…”
Section: Endpoints Indications and Selection Of Routementioning
confidence: 99%
See 1 more Smart Citation